Developing Tourism in Hoa Binh Province in the Context of International Economic Integration - Hien, Tran Thi; Hoa, Ho Thi; Hanh, Nguyen Thi Hong; Hoa, Nguyen Thi Minh; Thao, Nguyen Thi Phuong (Archives of Business Research, 2023)
According to a report from the Department of Culture, Sports and Tourism, in the first 6 months of 2023, the total number of tourists coming to Hoa Binh is about 2,360,000, increasing by 28.8% compared to the same period last year, reaching 67.4% of the year plan. Of which, there were 240,000 international visitors, an increase of 336% compared to the same period last year, reaching 53.3% of the year's plan; 2,120,000 domestic visitors, an increase of 19.3% compared to the same period last year, reaching 69.5% of the year's plan. Total revenue from tourists reached 2,300 billion VND, an increase of 16.2% compared to the same period last year, reaching 59% of the year plan. The above impressive recovery results after the COVID-19 pandemic are thanks to the province's tourism industry having synchronously deployed many groups of tasks and solutions to develop destinations, building tours, and attractive tourism product groups and organize a variety of activities to attract the attention of domestic and foreign tourists, creating a premise for tourism to recover and maintain operations in the last months of the year and the following years. The article focuses on analyzing and evaluating the current status of Hoa Binh tourism development in the period 2018 - 2022 and proposes some solutions to promote the development of the province's tourism industry in the context of international economic integration.